POTENSI PEMANFAATAN MIKORIZA UNTUK MENINGKATKAN KETAHANAN PANGAN - Lumbantoruan, Santa Maria; Herlina, Herlina; Az-zahra, Risma Chantrika (LPPM Universitas Bina Insan, 2020)
This study aims to examine the mycorrhizal potential for food security in Indonesia. The analysis is based on literature review using secondary data as a source of information. Food productivity has an important role in the lives of many people. Meanwhile, on the one hand, we are faced with immeasurable human growth and land functions that have begun to shift to settlements over time. One way to increase food in Indonesia is to empower marginal lands. Indonesia has a marginal land area that has not been optimized due to problems with the soil, poor nutrients and poor water management. Of course, to overcome this, it is necessary to have an agricultural cultivation approach so that these lands can be utilized. One of the approaches to agricultural cultivation is the application of biological fertilizers, namely mycorrhizae. From several literature studies, it is found that mycorrhizae can increase plant production by increasing nutrient uptake in marginal lands.